Detergent-inhibited, heat-labile nucleoside triphosphatase in cores of avian myeloblastosis virus. - Jensen, K F (1978)
Endogenous DNA synthesis was studied in isolated core particles of avian myeloblastosis virus. It was found that cores contained an enzymatic activity which rapidly converted the added nucleoside triphosphates to diphosphates (but not further) at 0 degrees C, thus inhibiting DNA synthesis. This triphosphatase probably originates from the viral membranes. In the cores the enzyme is completely inactivated by low concentrations (0.02%) of Nonident P-40. Also, the enzyme is very thermolabile and denatures rapidly at 38 degrees C.